Stories of "Self". Ideology in action. - Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2024)
Theory about “self” is political. It immediately situates a person’s problems within an individual, and/or within wider social systems. This paper encourages therapists to be curious about their stories of “self” and about the ideologies that produce them. By taking responsibility for one’s preferred stories (theories) of “self”, we can understand and take responsibility for therapeutic theory and practice as cultural products, products which create social consequences. Many therapeutic theories frame the problems that people have as indicators of personal inadequacy. These theories are at work within the therapeutic relationship, a relationship of unequal power. The storying of people and their struggles by professionals is frequently a one-sided imposition of theory and values by one party (the professional) on another (the client). In this sense, therapeutic relationships have the potential to colonise. This is particularly worrying given many people look to therapy to support their journey in overcoming experiences of being colonised in other contexts. A table shows a sample of psychotherapeutic modalities. It contrasts the different ideologies and the stories of self they produce. Different levels of context (Afuape, 2012; Oliver, 1996; Pearce, 2002; Pearce and Cronen, 1980) show how different ideologies play out in therapeutic practice, and how therapy maintains or disrupts social change. Beyond the table, there are questions at each level of context for therapists to explore how their own subscription to specific ideologies has implications for their therapeutic practice, supervision and training The paper ends with a reflection on how theorethical reflexivity could move the levels of context into a fluidly reflexive process which involves being prepared to change an ideology so that theories of self are contextually responsive and intentionally decolonising (Afuape, 2012; Reynolds, 2010).